Healthcare service delivery to refugee children from the Democratic Republic of Congo living in Durban, South Africa: a caregivers’ perspective - Meyer-Weitz, Anna (BMC Med, 2018)
BACKGROUND: Refugees are generally considered a vulnerable population, with refugee children (newborn and young children) being particularly so. Access to healthcare for this population remains a challenge. The main purpose of this study was to explore refugee caregivers’ perceptions of their children’s access to quality health service delivery to their young children in Durban, South Africa. METHODS: This study used an explanatory mixed methods design, purposively sampling 120 and 10 participants for the quantitative and qualitative phases, respectively. Participants were administered a self-developed questionnaire that assessed demographic information of participants, socioeconomic status and living standard, medical history of children, satisfaction and experiences with healthcare services and refugees’ networks and social support. A semi-structured interview schedule was developed to elicit in-depth and more detailed information from the participants on the quantitative areas that were investigated. Frequencies were calculated and a χ(2) test was used to explore the factors associated with refugees’ satisfaction of the healthcare provided and thematic analysis was used to analyse the qualitative data. RESULTS: The majority (89%) of caregivers were women, with over 70% of them aged between 30 and 35 years. Over 74% of caregivers visited public clinics for their children’s healthcare needs. The majority of caregivers (95%) were not satisfied with healthcare services delivery to their children due to the long waiting hours and the negative attitudes and discriminatory behaviours of healthcare workers, particularly in public healthcare facilities. CONCLUSION: These findings underscore the need to address health professionals’ attitudes when providing healthcare for refugees. Attitudinal change may improve the relationship between service providers and caregivers of refugee children in South Africa, which may improve the health-related outcomes in refugee children. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12916-018-1153-0) contains supplementary material, which is available to authorized users.